SOIL DEHYDROGENASE ACTIVITY: A COMPARISON BETWEEN THE TTC AND INT METHOD. A REVIEW - Susan Marlein Mambu (JURNAL ILMIAH SAINS, 2014)
ABSTRACT Soil enzyme activities are very sensitive to both natural and anthropogenic disturbances and show a quick response to the induced change. Soil dehydrogenase enzyme are one of the main components of soil enzymatic activities participating in and assuring the correct sequence of all the biochemical routes in soil biogeochemical cycles. Dehydrogenase activity is measured by two methods using the TTC and INT substrate. Different biotic and abiotic factors such as incubation time and temperature, pre-incubation, soil aeration and moisture content have significant effect on dehydrogenase activity in soil. Dehydrogenase enzyme is often used as a measure of any disruption caused by pesticides, trace elements or management practices to the soil, as well as a direct measure of soil microbial activity. This review describes the role of intracellular enzyme-dehydrogenase in the soil environment, and the most common laboratory procedure used for measure dehydrogenase activity by two methods using the TCC and INT substrate. Keywords: Dehydrogenase Activities, Flooded Soils, Soil Quality Â  AKTIVITAS DEHIDROGENASE TANAH: KAJIAN PERBANDINGAN ANTARA TTC DAN METODE INT ABSTRAK Â  Aktivitas enzim tanah sangat sensitif terhadap gangguan yang disebabkan oleh alam dan antropogenik dan menunjukkan respon yang cepat terhadap perubahan yang terjadi. Enzim tanah dehidrogenase adalah salah satu komponen utama dari aktivitas enzim tanah yang berpartisipasi dalam siklus biogeokimia tanah. Aktivitas dehidrogenase dapat diukur dengan menggunakan dua metode TTC dan INT substrat. Perbedaan faktor biotik dan abiotik seperti waktu inkubasi dan suhu, pre-inkubasi, aerasi tanah dan kadar air memiliki pengaruh yang signifikan pada aktivitas dehidrogenase dalam tanah. Enzim dehidrogenase sering digunakan sebagai ukuran dari gangguan yang disebabkan oleh pestisida, elemen atau manajemen pengelolaan tanah, serta dapat mengukur langsung aktivitas mikroba tanah. Ulasan ini menjelaskan peran enzim dehidrogenase intraseluler dalam lingkungan tanah, dan prosedur laboratorium yang paling umum digunakan untuk mengukur kegiatan dehidrogenase, yaitu dengan menggunakan metode TTC dan INT substrat. Kata Kunci: Aktivitas Dehidrogenase Tanah, TTC, INT